Studying Neutrophil Function in vitro: Cell Models and Environmental Factors - Blanter M; Gouwy M; Struyf S (Dove Medical Press, 2021)
Marfa Blanter, Mieke Gouwy, Sofie Struyf Laboratory of Molecular Immunology, Department of Microbiology, Immunology and Transplantation, Rega Institute for Medical Research, University of Leuven, Leuven 3000, BelgiumCorrespondence: Sofie Struyf Rega Institute - Herestraat 49 – Bus 1042, Leuven 3000, BelgiumTel +32 16 32 24 22Email sofie.struyf@kuleuven.beAbstract: Neutrophils are the most abundant immune cell type in the blood and constitute the first line of defense against invading pathogens. Despite their important role in many diseases, they are challenging to study due to their short life span and the inability to cryopreserve or expand them in vitro. Thus, research into neutrophils has to rely on cells freshly isolated from peripheral blood of human donors, introducing donor-dependent variation in the experimental data. To counteract these problems, researchers tried to develop adequate cell models, such as cell lines. For those functional studies that cannot rely on cell models, a standardization of protocols regarding neutrophil purification and culturing could be a solution. In this review, we provide an overview of the most commonly used models for neutrophil function (HL-60, PLB-985, NB4, Kasumi-1 and induced pluripotent stem cells). In addition, we describe the effects of glucose concentration, pH, oxygen tension and temperature on neutrophil function.Keywords: neutrophils, HL-60, PLB-985, NB4, Kasumi-1, induced pluripotent stem cells